2021
DOI: 10.3390/jcm10061152
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Silver Nanoparticles as Root Canal Irrigant’s: A Systematic Review

Abstract: Removal of microbes is imperative during endodontic therapy. Due to their antimicrobial property, silver nanoparticles have been used for endodontic irrigation of the root canals. The objective of the present study was to provide a qualitative analysis of the published literature assessing silver nanoparticles as root canal irrigants. A search of PubMed, SCOPUS, Web of Science, and Embase databases was done without any time restriction. Articles published in English were included. Data were extracted and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…What more, due to antibacterial effect these materials may be useful for various biomedical application, i.e. as antimicrobial and disinfect agent, or to prepare the antiseptic layers 85 87 . Simultaneously, the same nanomaterial, depends on the concentration used, could be a great platform for targeted drug delivery, as well as to combat with cancer cells 88 , 89 .…”
Section: Resultsmentioning
confidence: 99%
“…What more, due to antibacterial effect these materials may be useful for various biomedical application, i.e. as antimicrobial and disinfect agent, or to prepare the antiseptic layers 85 87 . Simultaneously, the same nanomaterial, depends on the concentration used, could be a great platform for targeted drug delivery, as well as to combat with cancer cells 88 , 89 .…”
Section: Resultsmentioning
confidence: 99%
“…NaOCl is the current gold standard for root canal chemical disinfection [ 48 ]. The antibacterial effects of irrigants, e.g., NaOCl, CHX, and AgNPs depend on their concentration [ 13 ], contact time, and contact surface area [ 49 ]. Ioannidis et al (2019) reported the efficacy of AgNPs synthesized on an aqueous matrix of graphene oxide (GO) in the elimination of microorganisms and biofilm in an infected tooth model.…”
Section: Application Of Agnps In Endodonticsmentioning
confidence: 99%
“…Silver ions taken in the cell can cause malfunction of respiratory enzymes, causing responsive oxygen groups to form and adenosine triphosphate production to be disrupted. Direct denaturation of DNA and ribosomes can also be caused by silver ions [55]. Since it successfully dissolved E. faecalis biofilm and removed the bacteria from infected dentinal tubules, the Ag NP solution is an effective root canal irrigant [30].…”
Section: Ag Nps Used In Endodonticsmentioning
confidence: 99%